American Urogynecologic Society Prolapse Consensus Conference Summary Report. Issue 4 (July 2018) - Siddiqui, Nazema Y.; Gregory, W. Thomas; Handa, Victoria L.; DeLancey, John O.L.; Richter, Holly E.; Moalli, Pamela; Barber, Matthew D.; Pulliam, Samantha; Visco, Anthony G.; Alperin, Marianna; Medina, Carlos; Fraser, Matthew O.; et al.
Abstract : Objectives: The 2016 American Urogynecologic Society Prolapse Consensus Conference brought together thought leaders in the field of pelvic organ prolapse (POP). The goal was to identify critical areas of need for future research. This article summarizes the findings. Methods: Prior to the conference, 5 major focus areas were identified. Focus areas were explored over the 2-day conference. Clinicians, clinical and basic science researchers, and representatives from government agencies, industry, patient advocacy groups, and the public convened to identify the major gaps in knowledge in each of these focus areas. Results: The 5 major topics were as follows: (1) mechanistic research on pelvic supportive structures and how these are altered with pregnancy, delivery, and aging; (2) novel prostheses or implants that address pathophysiology and provide mechanical support; (3) large-scale community-based research; (4) clinical trials to optimize outcomes after POP surgery; and (5) evidence-based quality measures for POP outcomes. Key recommendations were made for each topic. Conclusions: Critical gaps in our knowledge were identified. These limit scientific discovery across all 5 topic areas. Further scientific progress would be advanced by (1) developing a standardized group of POP outcomes and quality measures for large trials and community-based research, (2) creating specimen biorepositories that are integrated with robust clinical data, and (3) developing collaborative teams with expertise from a variety of disciplines, convened to tackle our most challenging and complex scientific questions.